Bilingualism in Slovenian Istria: Studies and Issues in Its Preservation - Kompara Lukančič, Mojca; Lenassi, Nives; Paolucci, Sandro (University of Maribor Press, 2023)
The volume starts with an overview chapter of studies on bilingualism and bilingual individuals in general, and the particular aspects and characteristics of bilingualism in Slovenian Istria. It continues with three chapters focusing on Italian in the bilingual area of the Slovenian coast. The second chapter presents surveys on the position of bilingualism, the influence of Italian media, the results of the secondary school leaving exams in Italian, and the status of bilingualism in Slovenian schools in the bilingual Littoral communities. The third chapter offers an analysis of texts and documents translated from Slovenian into Italian; that is, bilingual texts available on the websites of the four bilingual municipalities: Koper, Izola, Piran, and Ankaran. The final chapter presents some detailed aspects of studies carried out on administrative texts of the bilingual municipalities, focusing on selected lexical units and acronyms, and offering translation solutions that guarantee and preserve minority rights and offer uniform terminology.